INVESTIGATING STUDENT’S CRITICAL THINKING DISPOSITION BASED ON GENDER IN PHYSICS TEACHING WITH INTERACTIVE MULTIMEDIA - Gunawan, Gunawan; Harjono, Ahmad; Herayanti, Lovy; Husein, Sadam; Fathoroni, F (JPPS (Jurnal Penelitian Pendidikan Sains), 2019)
Interactive multimedia is able to combine various kinds of representations into one whole media unit. These representations are in the form of visual, auditory, and procedural representations. Interactive multimedia capabilities can directly stimulate the development of students' critical thinking skills. This research has explored the increasing tendency of students to think critically or called critical thinking disposition. In particular, this study compared the increasing levels of critical thinking disposition of male and female students. Field trials employed a quasi-experiment with a pretest and posttest control group design. The subject consisted of 16 male and 16 female students in senior high school at Mataram, Indonesia. The research instrument used description problem that has been adapted to the indicators of critical thinking disposition, namely truth-seeking, open-mindedness, analyticity, systematic, and inquisitiveness. The results indicate that of N-gain research for male students were 35.5 and female 36.4. This shows that the use of interactive multimedia has a positive effect on improving critical thinking disposition in both male and female students.